Risk factors for the development of low back pain: an overview of systematic reviews of longitudinal studies. (4th May 2018) - Krishnamurthy, Ilanchezhiyan; Othman, Rani; Baxter, George David; Mani, Ramakrishnan
Abstract : Objective: To conduct an overview of systematic reviews on risk factors for the development of non-specific LBP and critically appraise the level of evidence for those risk factors. Methods: Systematic reviews on risk factors for LBP were searched in the following electronic databases: EMBASE (via Ovid), Medline (via Ovid), CINAHL (EBSCO), AMED, PsycINFO (via Ovid), Scopus, Web of Science (via Web of Knowledge), ProQuest Central, PEDro and The Cochrane Library. Two reviewers independently screened the reviews that investigated primary longitudinal studies on risk factors associated with non-specific LBP including only LBP free subjects at baseline assessment period. Database search resulted in 438 studies, of which 5 SRs met our criteria. Inter-rater reliability between the reviewers were observed as substantial ( k = 0.76). First reviewer extracted the risk factors along with risk estimates and study characteristics and the data was cross checked by the second reviewer. The methodological quality of the SRs was evaluated using AMSTAR tool. A two-staged procedure was performed to determine the level of evidence. Results: Eleven risk factors found to have moderate evidence: lifting ≥25 lb (females); standing for >2 h (females); history of LBP ≥1 month duration and ≤1 year since LBP onset; previous history of frequent LBP; poor general health; childhood status including psychosocial difficulties, abdominal pain >7 days/month, carrying out part-time job, spine asymmetry (females), >18 versus <5 h of sports activities/week, lumbar extension mobility: lumbar extensor muscle endurance ratio. Conclusion: This overview of systematic reviews concluded that there is no potential risk factor with strong evidence for the development of LBP. Posture, history of LBP, other pain conditions and sports and leisure activities are the risk factors found to have moderate evidence for the development of LBP.